The increased feminization of the surfing economy: An exploration of the lived experiences of female surfers in Muizenberg, South Africa - Stroehlein, Leonie Victoria (School of Management Studies, 2022)
This thesis is a phenomenological exploration of female surfers' lived experiences in the surfing culture and economy of Muizenberg, South Africa. The research design includes a review of literature, participant observation and semi structured in-depth interviews. The approach was qualitative so as to gain deep insights into women's lived experiences participating in a predominantly male sporting culture and economy. Thereby, the everyday experiences, feelings, victories and constraints of female surfers were central to the investigation. Even though some athletes showed active resistance to gendered identities and contest stereotypical femininities, this research demonstrates that females still feel marginalized in what they see as the continued male-dominant sport of surfing. The results reveal that identity creation of female surfers is influenced by the media representation of women as well as the masculinity of the sport. The female surfers of the study face structural, interpersonal as well as intrapersonal constraints in their surfing lives. It is striking that most of the interpersonal constraints refer to attitudes of male surfers towards women. Furthermore, it has been revealed that female surfers are active participants in and drivers of the surfing economy. However, women often are socially and economically devalued and continue to be a minority in the surfing community. There is little to suggest that female surfers' constraints and gendered identity creation at Muizenberg will change significantly as long as there is no combined effort of media, professional surfing organizations and men in positions of influence to work towards an improvement of support for female surfers from beginner to professional. In order to move towards advancing female surfing, gender equality has to be addressed across multidimensional structures.